SNP-based discrimination of pink salmon stocks of the Sea of Okhotsk basin: resolution of the approach and possible ways to increase it - Zelenina, Daria A.; Sergeev, Alexey A.; Kositsina, Anna I.; Soshnina, Valeria A.; Shpigalskaya, Nina Yu. (Frontiers in Marine Science, 2023)
In this work, we studied the intraspecific polymorphism of pink salmon, Oncorhynchus gorbuscha (Walbaum, 1792), the least genetically explored species among Pacific salmon and one of the central fisheries objects in the Russian Far East. The most urgent task facing Russian fishery science is to determine the proportion of fish from the main reproduction areas in mixed stocks and, based on these data, predict the number of pink salmon returning to these regions for spawning. Due to the unique feature of the species, which evolved into two allochronous lineages, these lineages have been explored independently in parallel. We designed and used here two sets of outlier SNP markers, and this allowed us to reliably distinguish the most northern (Western Kamchatka and the Magadan coast) and the most southern (Iturup Island) regional stocks as well as intermediate stocks from Sakhalin Island and the Mainland coast in both even and odd lineages of pink salmon. In addition, in odd-year lineage, we discovered pronounced genetic differences between early-run and late-run spawners in Sakhalin Island and the proximity of this early spawning form to the mainland stocks. The created baseline covers the main areas of pink salmon reproduction in the Sea of Okhotsk basin and underlies the regional identification of pink salmon in mixed marine stocks.